2006
DOI: 10.1086/500108
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Progenitor of Cassiopeia A

Abstract: We compare a suite of three-dimensional explosion calculations and stellar models incorporating advanced physics with observational constraints on the progenitor of Cassiopeia A. We consider binary and single stars from 16 to 40 M with a range of explosion energies and geometries. The parameter space allowed by observations of nitrogen-rich highvelocity ejecta, ejecta mass, compact remnant mass, and 44 Ti and 56 Ni abundances individually and as an ensemble is considered. A progenitor of 15-25 M that loses its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
198
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(217 citation statements)
references
References 48 publications
(68 reference statements)
15
198
2
Order By: Relevance
“…However, it is not clear whether the low ejecta mass is due to heavy mass loss of a single massive star that was on its way, or just entered the WR phase, or whether mass loss was induced by a common envelope phase in a binary system (Young et al 2006). Also the presence of a jet-counterjet system in Cas A (Vink 2004;Hwang et al 2004) puts strong constraints on the duration of a possible WR phase (Schure et al 2008).…”
Section: Send Offprint Requests To: B Van Veelenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not clear whether the low ejecta mass is due to heavy mass loss of a single massive star that was on its way, or just entered the WR phase, or whether mass loss was induced by a common envelope phase in a binary system (Young et al 2006). Also the presence of a jet-counterjet system in Cas A (Vink 2004;Hwang et al 2004) puts strong constraints on the duration of a possible WR phase (Schure et al 2008).…”
Section: Send Offprint Requests To: B Van Veelenmentioning
confidence: 99%
“…García-Segura et al (1996) suggested that these knots are the remnants of the broken up WR shell. Note that also a binary common envelope phase is likely to be followed by a WR-like mass loss phase (Young et al 2006). Both the fact that the QSF lie within the boundary of the forward shock, and the inferred density behind the forward shock of Cas A, limits the possible duration of a WR phase to ∼ 10 4 yr (García-Segura et al 1996).…”
Section: Send Offprint Requests To: B Van Veelenmentioning
confidence: 99%
“…First, given the association of a SN remnant with a relativistic object, one can attempt to infer the properties of the progenitor object from the former; a classic example being the Crab nebula (Nomoto et al 1982). However, this approach is model dependent, with Cas A, for example, being interpreted as originating from both single and binary progenitors of differing masses (Laming & Hwang 2003;Young et al 2006). Second, theoretical reconstruction of the evolutionary history of (high-mass) X-ray binaries such as GX301-2 (=BP Cru) and 4U1700-37 (=HD 153919) from their current physical properties may be attempted (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Energy to eject the envelope is extracted from the orbital energy, but a small layer of hydrogen may remain on the surface of the merger product until the moment of explosion as a supernova type IIb. This scenario was recently considered by Young et al (2006) for Cassiopeia A, in which no evidence for a companion star was found, despite numerous attempts.…”
Section: Introductionmentioning
confidence: 99%